KARYA DAN PEMIKIRAN KYAI RADEN ASNAWI KUDUS - Linda Linda Musyarofah (TASAMUH, 2022)
Kyai Raden Asnawi was born and raised in a merchant environment as well as in the Islamic boarding school tradition. Since childhood, he studied at various ulama and Islamic boarding schools. He had studied and taught in Mecca for 22 years (1894-1916). The purpose of this study is to better understand the genealogy and Islamic thought of Kyi Raden Asnawi and the struggle in preaching. This research is a qualitative research with the type of library research (library resach). The data analysis technique used is by collecting data from books, presenting and concluding. While the results of this study are, 1) Kyai Raden Asnawi's biography, 2) Kyai Raden Asnawi's thoughts which are contained in various books and poems, including aqidah (tawhid), fiqh, and tasawuf, according to the conception of ahlussunnah wal jama'ah. In teaching at madrasas, to strengthen the faith and shari'a of Muslims, he compiled a book of faith called Mu'taqod Seket and a book of fiqh called Fasholatan. In the field of aqidah (theology), he adheres to the conception formulated by Imam Al-Asy'ari and Imam Al-Maturidi, in the field of fiqh (Islamic law), he follows the Imam Shafi'i madhhab, while in the field of Sufism (sufism), he followed orthodox Sufism formulated by Imam Junaid Al-Baghdadi and Imam Al-Ghazali.